Biogeochemical tools for characterizing organic carbon in inland aquatic ecosystems. Issue 6 (30th October 2018) - McCallister, S. L.; Ishikawa, N. F.; Kothawala, D. N.
Abstract: Integration of inland waters into regional and global carbon (C) budgets requires a comprehensive understanding of factors regulating organic carbon (OC) delivery and in situ processing. This study reviews advances in optical, molecular, and isotopic approaches to resolve the sources, ages, and transformations of OC in aquatic systems. OC characterization using excitation emission matrix spectra, Fourier transform ion cyclotron mass spectrometry, and nuclear magnetic resonance provides detailed molecular level insight. Radiocarbon isotopic approaches and compound‐specific techniques resolve the input, metabolic fate, and turnover time of OC in ecosystems ranging in size from streams to the open ocean. Accumulating evidence suggests that aquatic OC is composed of diverse biogeochemical components. We conclude with enduring and emerging questions that underscore the role of inland systems in the global C cycle and propose unique combinations of approaches to better discern their role in the delivery and transformation of OC from soils to seas.